The Need for Sociotechnical Turn in the Study of Society Digitalization - Karpova, Daria; Proskurina, Alexandra (KnE Social Sciences, 2021)
This study investigates the conditions of digital society development. All probable unintended consequences of digitalization require the development of a science-based approach to manage this digital development. However, there is a problem associated with the divergence in the assessment of the digitalization effects by representatives of the information technology sector responsible for the new technologies development and by representatives of social sciences studying the impact of digitalization on social relations, institutions and processes. Authors propose a new approach to understanding new digital reality based on so-called sociotechnical turn, which is a purely integrative approach aimed at solving a tough common issue. Moreover, the article proposes a theoretical analysis of sociological and technological discourses of the society digitalization problem. To define and structure the set of differences, there were conducted 5 in-depth interviews with specialists from the technical field, aiming to gather information both from applied experts and more science-oriented participants. The study has revealed that those who perform tasks set under the digitalization agenda may not be aware of the social consequences of their work. They follow a linear technical logic of computers and do not consider ethical or more complex social issues in their daily activity. This discovery supports our claim that it is of paramount importance to separate terms of digitization, meaning a technical view of the issue, and digitalization, implying a cross-field approach including both social and technical sciences. Keywords: digitalization, digital society, sociological turn, technology, social digitalization